Photophysical Studies of α,ω-Dicyano-oligothiophenes NC(C4H2S)nCN (n = 1−6) - Pina, J. (2006)
The photophysics of six oligothiophenes end-capped with cyano groups (CNαn) was investigated in solution at room and low temperature. The study comprises singlet−singlet and triplet−triplet absorption and emission spectra together with lifetimes and quantum yields for all the radiative and nonradiative processes. From the lifetimes and quantum yields, it was possible to extract the rate constants for all the processes. Singlet oxygen yields were also determined, revealing an efficient sensitization (SΔ ≈ 1) of its formation by the triplet state of the CNαn. The introduction of the cyano groups is found to decrease the energetic separation between the highest occupied molecular orbital and the lowest unoccupied molecular orbital, leading to a red shift of the absorption and the emission when compared with the unsubstituted counterparts, the α-oligothiophenes. Phosphorescence is only observed for the first member of the series, CNα1.